Relationship between sport preferences and personality / Redzwan Nazly Razali Chong - Razali Chong, Redzwan Nazly (2011)
Performance and achievements of athletes could be attributed to four major factors that consist of natural inherited ability, acquisition of skill, physical fitness level and socio-psychological elements such as personality and emotional strength. However, personality has always been a topic of interest for research in terms of its relationship with sport preferences and performance. Athletes in general are not aware of their own behavior and personality. Thus, it creates a barrier for them to perform at their level best. In relation to that, the absence of knowledge of recognizing the personalities of athlete may create a hurdle of communication flow between coaches and athletes. In order to have a good breed of athletes in the future, personality should be included as part of an assessment during talent identification process. Hence, this research was conducted with the aim to determine whether there is a relationship between types of personality and sport preferences. The objectives of this study were to compare the different types of personality to gender, types of event and types of sport. The study was conducted using three different sets of questionnaires from Eysenck Personality Questionnaire, Global 5 / SLOAN Personality Test and Impulsive Sensation Seeking Scale (ImpSS). 229 subjects of this study were athletes from 29 different sports who represented in Malacca’s Malaysia Games 2010 team. The subjects consist of 154 males and 75 females aged from 13 to 21 years old. The questionnaires were then collected and analyzed using Independent Samples T-Test and ANOVA in SPSS. The results indicated that there is a significant difference for gender in terms of extroversion and neuroticism. Male are higher in extroversion whereas female are higher in neuroticism. Following that, a significant difference between the different types of sport tested was also on extroversion. The sports that are recognized to go well with extroverts are Acrovolley, Weightlifting, Canoe, Rugby, Softball and Fencing. Considering there was more participants from male to female, results may be skewed due to the lack of proportionality.